Aviation industry in global perspective - Veselý, Martin; Jílek, Josef, 1957-; Bertoli, Paola; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The hypothesis claims that full service carriers (FSCs) will be forced to change their operating models. Additionally, the trends which form aviation market of the future are explored. The investigation is based on a financial assessment of ten important airlines incorporated in four different regions across the globe, between 2005 and 2014. According to the findings the trend of liberalization will continue, thus FSCs will continue losing market share to low cost carriers (LCCs) and as such, they will be made to change the way they operate in order to survive. The future aviation market is defined by a reshuffle of demand towards emerging countries, further rationalization of operating models and consolidation.
Vedoucí práce: Josef Jílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses